2018
DOI: 10.1177/0954409718802998
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the electromagnetic environment on the railway: Condition monitoring of signalling assets

Abstract: Conventional track circuit condition monitoring systems are fixed at the wayside, with each installation reporting on a single track circuit. In this work, we present a custom-built, sensitive, magnetic field detection system, which can be fitted to the underside of a rail vehicle. With this system installed, some characteristics of an operating track circuit can be monitored from the vehicle whilst it is in motion. By using appropriate analysis techniques, it is possible to identify the signatures of equipmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Niebling et al [ 371 ], staying in the mainstream of low-cost sensor applications—e.g., Knight-Percival et al [ 372 ]—on in-service trains, suggested deep learning ( artificial intelligence ) in order to analyze large volumes of sensors’ measurement data. The authors combined common signal processing methods and deep convolutional autoencoders and clustering algorithms.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Niebling et al [ 371 ], staying in the mainstream of low-cost sensor applications—e.g., Knight-Percival et al [ 372 ]—on in-service trains, suggested deep learning ( artificial intelligence ) in order to analyze large volumes of sensors’ measurement data. The authors combined common signal processing methods and deep convolutional autoencoders and clustering algorithms.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…Moreover, the authors mentioned that thermal changes impact both rail surface and pantograph catenary; therefore, they suggested the coupling of fuzzy and thermal image processing methods. Moreover, in Knight-Percival et al [ 372 ], the authors observed that the interdisciplinary field of systems engineering—in particular transportation systems—is extended and supported by Industry 4.0 . Industry 4.0, according to the authors, focuses on the design and management of complex systems during their life cycles, with consideration of four design principles—namely, interoperability (communication and connection between systems, devices, and sensors), information transparency (integration of sensor data with a digital twin of a physical system), technical assistance (visualization of complex data and reduction of workload), and decentralized decisions (autonomy of complex systems that can adapt to the specific environment).…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Since typical railway infrastructure has a lifetime of 30–40 years, rolling technology upgrades also occur over long timescales. Meanwhile, DC track circuits (of the kind we are modeling) are relatively cheap and there are thousands installed in the UK network that will remain in use for decades to come (Knight‐Percival et al., 2020).…”
Section: Track Circuit Signalingmentioning
confidence: 99%
“…Since typical railway infrastructure has a lifetime of 30-40 years, rolling technology upgrades also occur over long timescales. Meanwhile, DC track circuits (of the kind we are modeling) are relatively cheap and there are thousands installed in the UK network that will remain in use for decades to come (Knight-Percival et al, 2020).…”
Section: Track Circuit Signalingmentioning
confidence: 99%